2014
DOI: 10.1016/j.precamres.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Neoproterozoic subduction along the Ailaoshan zone, South China: Geochronological and geochemical evidence from amphibolite

Abstract: a b s t r a c tLenses of amphibolites occur along the Ailaoshan suture zone at the southwestern margin of the Yangtze Block, South China. Petrological, geochemical and zircon U-Pb geochronological data indicate that they are divisible into two coeval groups. Group 1, represented by the Jinping amphibolite, has mg-number of 71-76 and (La/Yb)cn ratios of 7.2-7.7, and displays a geochemical affinity to island arc volcanic rocks. Group 2 amphibolites occur at Yuanyang and are characterized by high Nb contents (14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 118 publications
(93 reference statements)
3
27
1
Order By: Relevance
“…Wang et al, 2014). It is worthy to note that although previous studies on intrusions (e.g., Cai et al, 2014) indicate that most Neoproterozoic zircons in western margin of the Yangtze Block have positive εHf(t) values, both positive and negative εHf(t) values are shown for the detrital zircons with Neoproterozoic ages in our study. Previous detrital zircon data have also shown that Neoproterozoic zircons have both positive and negative εHf(t) values (e.g.…”
Section: Western Yangtze Margincontrasting
confidence: 66%
See 3 more Smart Citations
“…Wang et al, 2014). It is worthy to note that although previous studies on intrusions (e.g., Cai et al, 2014) indicate that most Neoproterozoic zircons in western margin of the Yangtze Block have positive εHf(t) values, both positive and negative εHf(t) values are shown for the detrital zircons with Neoproterozoic ages in our study. Previous detrital zircon data have also shown that Neoproterozoic zircons have both positive and negative εHf(t) values (e.g.…”
Section: Western Yangtze Margincontrasting
confidence: 66%
“…1) (Z. Zhu et al, 2006;Zhao and Zhou, 2007;Zhu et al, 2008;Cai et al, 2014) and intermediate-acid intrusions (Fig. 1) (Li et al, 2002;Zhou et al, 2002a;X.…”
Section: Western Yangtze Marginmentioning
confidence: 97%
See 2 more Smart Citations
“…The age group matches temporally with the breakup of the supercontinent Rodinia (Li et al, 2008), which is responsible for the fact that Neoproterozoic magmatism was widespread in the Yangtze block, especially in the Jiangnan orogen ( Fig. 9d and e), but scarce in the southern NCB (e.g., Cai et al, 2014Cai et al, , 2015Wang et al, 2010;Zhang and Zheng, 2013;Zheng, 2003;Fig. 9a).…”
Section: Provenance Of the Sedimentary Rockssupporting
confidence: 61%